Jewish Physicians' Beliefs and Practices Regarding Religion/Spirituality in the Clinical Encounter - Stern, Robert M. (Journal of religion and health, 2011)
We used data from a 2003 survey of US physicians to examine differences between Jewish and other religiously affiliated physicians on 4-D of physicians' beliefs and practices regarding religion and spirituality (R/S) in the clinical encounter. On each dimension, Jewish physicians ascribed less importance to the effect of R/S on health and a lesser role for physicians in addressing R/S issues. These effects were partially mediated by lower levels of religiosity among Jewish physicians and by differences in demographic and practice-level characteristics. The study provides a salient example of how religious affiliation can be an important independent predictor of physicians' clinically-relevant beliefs and practices.